CITIZEN REPORTING SYSTEMS IN THE GLOBAL AND CZECH SPECIFIC VIEW - Kopáčková, Hana; Líbalová, Petra (Žilinská univerzita, 2018)
Urban areas have to face many problems rising from the concentration of people on limited space. Solving these problems is a matter for the public administration, especially those serious issues as unemployment, security, scarcity of housing, air pollution, etc. However, digital technologies enabled citizens to participate on solving some issues visible to them. Citizen reporting systems offer citizens fast and very simple way to draw attention to a problem in a particular territory (damaged benches, mess, broken pavement, uncut grass, landfills, etc.). We can distinguish mainly three types of citizen reporting systems: web based; module, which is part of city mobile application; and specialized mobile application for issue reporting. Such systems use citizens as sensing devices gathering data that help cities make their operations more flexible. This way of participation activates people to care about place they live - their city. Smart cities need active people who care and feel responsible for the city that is why the participation is one of main pillars of smart cities. Through the literature review, this article summarizes the use of citizen reporting systems in the global context and compares it with the situation in the Czech Republic. Analysis of city applications of regional capitals reveals if they use some citizen reporting system and if yes, which types do cities use.
Systém pro hlášení občanů na úrovni globální i České republiky
Keywords: participation, technology, cities, citizen reporting systems, citizens; participace; technologie; města; systém pro hlášení závad, občané